POTENSI PENCEMARAN DARI LIMBAH CAIR INDUSTRI PENGOLAHAN IKAN DI KECAMATAN MUNCAR, KABUPATEN BANYUWANGI - Setiyono, Setiyono; Yudo, Satmoko (Jurnal Air Indonesia, 2008)
Fish processing industries in Muncar-Banyuwangi have increased the welfare of the people there and made this area known as the major fish producer in Indonesia. More than 50% of its production has been exported to many countries and the rest has fulfilled domestic need. Although fish processing industry has developed quickly, its industrial pollution effect hasn’t been handled well so that it polluted the surrounding envionment especially water surface. It happened because of using water for industrial need reached 17.883,2 m3 /day and almost all industries haven’t provided a good wastewater installalion so that the environment couldn’t handle and neutrilize the wastes. This paper explains condition of fish processing industries and potential load of the wastewater produced by them. Keywords : Industri Pengolahan Ikan, Limbah Cair Industri, Pencemaran Lingkungan, Informasi.